The Degree to which Social Studies Teachers in the State of Kuwait Practice Creative Teaching Skills from their Point of View - Al-Ajmi, Mubarak Falah Hamid; Al-Ajmi , Muhammad Ali Rashid (Dirasat: Educational Sciences, 2023)
Objectives: To identify the degree of practice of creative teaching skills by social studies teachers in the State of Kuwait, and to identify if there are statistically significant differences in the degree of practice due to gender and academic qualification. Methods: The study used the descriptive quantitative research method. In order to answer the questions of the study, a questionnaire was prepared consisting of three domains: originality, fluency, and flexibility. It consists of (21) paragraphs. The questionnaire was distributed to a sample of (150) male and female teachers from government schools in the Al-Ahmadi educational district in Kuwait, who were chosen according to the stratified random method. Results: The degree of social studies teachers in the State of Kuwait practicing creative teaching skills from their point of view was high, as the total arithmetic mean for the domains was (3.84), and the field of fluency came in the first place with an arithmetic mean (3.89), and the field of flexibility came in the second place with an arithmetic mean (3.85), and the field of originality ranked third with an arithmetic mean (3.79). No significant gender differences were observed, but postgraduate teachers demonstrated a higher level of practice in their creative teaching skills. Conclusions: The study recommended the need to train teachers on creative teaching strategies that develop new unfamiliar methods in teaching social studies and to organize workshops and training programs for social studies teachers to enhance their utilization of creative teaching skills in educational settings.